Retinal detachment in chorioretinal coloboma – a challenge for the vitreoretinal surgeon - Zacharek, Olimpia; Murawska, Joanna (Klinika Oczna / Acta Ophthalmologica Polonica, 2021)
Chorioretinal coloboma is a rare, congenital condition of the eyeball. This anomaly of the eye is a result of improper differentiation of eyeball structures during the embryonic and fetal period. This malformation gives a high risk of other ophthalmic diseases such as choroidal neovascularization, glaucoma, cataract or – the most serious and the most common from all of these – retinal detachment. Proper and quick diagnostics, urgent treatment and cooperation with experienced vitreoretinal surgeons are necessary and can improve the prognosis. We present a clinical case report of retinal detachment in 23-year old patient with chorioretinal coloboma, hospitalized in the Department of Ophthalmology in University Clinical Centre in Gdansk, treated by pars plana vitrectomy with endolaser therapy and silicone oil endotamponade.